Demand-driven extension and advisory services: Catalysing opportunities for youth in agriculture - Franzel, Steven; Lowicki-Zucca, Jane; Miiro, Richard; Uwitonze, Nicolas; Davis, Kristin E.; Luzobe, Beatrice; Rurangwa, Raphael (DLG-Verlag GmbH, 2020)
While education access has improved globally, gains are uneven, and development impacts driven by increases in education continue to be left on the table, especially in rural areas. Demand-driven extension and advisory services (EAS) – as a key institution educating rural people while providing agricultural advice and supplying inputs – have a critical role to play in bridging the education gap. This can help ensure that millions of young people successfully capitalise on opportunities in agriculture markets, as surveys in Rwanda and Uganda demonstrate.